Regioisomeric α-[70]fullerene-fused lactones: Synthesis, characterization and solubility difference. Issue 51 (17th December 2020) - Li, Dan; Li, Zong-Jun; Li, Shu-Hui; Xu, Li-Jun; Gao, Xiang
Graphical abstract: Highlights: Two types of regioisomeric α -[70]fullerene-fused lactones were obtained. X-ray single crystal structures were obtained for the two types of regioisomers. A significant solubility difference is shown between the two types of regioisomers. New insight into the reaction mechanism is obtained. Abstract: Two types of regioisomeric α-[70]fullerene-fused lactones were synthesized from the reaction of C70 with 2-alkylmalonates under basic conditions. The structures of the compounds were determined unambiguously by X-ray single crystal diffraction analysis, and the compounds were further characterized with HRMS, UV–vis, 1 H NMR and 13 C NMR spectroscopies. The reactions were followed by the in situ vis-NIR measurement to study the mechanism. Interestingly, a large solubility difference was shown between the two types of regioisomers.